1991
DOI: 10.1159/000125980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 5-HT<sub>1</sub> and 5-HT<sub>2</sub> Receptor Antagonists on Insulin-Induced Adrenomedullary Catecholamine Release

Abstract: Previous works have indicated that insulin stress activates the serotonin (5-HT) and sympathoadrenal systems in the fasted rat. In addition, recent studies have shown that activation of either the 5-HT1A, the 5-HT1C or the 5-HT2 receptor triggers adrenal catecholamine release. Then, the aim of this study was to investigate whether brain 5-HT, by means of these receptors, mediates insulin-induced adrenal catecholamine release. For that purpose, both plasma epinephrine (Epi), nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Activation of a number of serotonergic receptors (5HT 1A , 5HT 1C , 5HT 2 , and 5HT 3 ) has been demonstrated to increase sympathetic nervous system outflow (5,6,38,39). Additionally, both systemic and central administration of SSRIs have specifically increased adrenal catecholamine and epinephrine release (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of a number of serotonergic receptors (5HT 1A , 5HT 1C , 5HT 2 , and 5HT 3 ) has been demonstrated to increase sympathetic nervous system outflow (5,6,38,39). Additionally, both systemic and central administration of SSRIs have specifically increased adrenal catecholamine and epinephrine release (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…6B). Since propranolol is a mixed ␤-adrenoceptor/5-HT 1A receptor antagonist (10,24), this result would imply that a catecholamine-cAMP or a serotonin-cAMP pathway in the PO is involved in anapyrexia. However, the observation that Rp-cAMPS failed to alter the thermoregulatory response to epinephrine (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As to the pharmacology of these agents, Rp-cAMPS and Rp-cGMPS are specific membrane-permeable inhibitors of protein kinases A and G, respectively, resistant toward cyclic nucleotide phosphodiesterases (3,8). As to propranolol, it is a mixed ␤-adrenoceptor/5-HT 1A receptor antagonist (10,24). Last, L-NMMA is a nonselective NO synthase inhibitor (25), whereas sodium nitroprusside is an NO donor, i.e., it has the property of releasing NO in biological systems (25).…”
Section: Animals and Drugsmentioning
confidence: 99%
“…Interestingly, in that same study, both 6 and 20 day treatment with sertraline prevented loss of the epinephrine response in recurrently hypoglycemic animals, suggesting loss of serotonergic neurotransmission may contribute to counterregulatory failure. In contrast, another study showed that treatment with either the 5-HT1C/5-HT2 serotonin receptor blocker, LY 53857, or the 5-HT1/5-HT2 receptor antagonist, metergoline, did not diminish plasma catecholamine responses to insulin-induced hypoglycemia 60 . Differences in these findings may be due to the length of treatment and/or the site of action of the compounds used.…”
Section: Serotoninmentioning
confidence: 92%